Market demand, routine activity, and illegal fishing: an empirical test of routine activity theory in Iran - Mir Mohamad Tabar, S. Ahmad (Deviant behavior, 2021)
Despite the presence of the punishment mechanisms in Iran’s criminal law to deal with illegal fishing, this crime remains a major problem in the country, threatening the sustainability of the targeted species and affecting the livelihoods of the communities that depend on it as a significant source of protein. Applying the lens of environmental criminology, specifically the routine activities approach, this research seeks to examine the major driving factors of illegal fishing in the Mazandaran Province in Iran. Data for this study were collected through a survey questionnaire administered to villagers in the city of Fereydunkenar. Using proportionated stratified random sampling, we collected data from 400 respondents on various variables designed to measure the routine activities constructs. Nearly 53% of respondents engaged in fishing without a license. Structural equation models indicate that the presence of a capable guardian, the presence of the economically motivated offender, and market demand had the greatest influence on illegal fishing. The market demand had significant direct effect on the economically motivated offender, who then engaged in illegal fishing. Policy implications are discussed in light of these findings.